Troubleshooting a Herd with a High Bacteria Count - David R. Bray (EDIS)
AN205, a 2-page fact sheet by David R. Bray, lists some common problems in dairy procedures which can cause a high bacteria count in a dairy herd. Published by the UF Department of Animal Sciences, June 2008.